Iron(II) modified natural zeolites for hexavalent chromium removal from contaminated water - Lofù Antonio; Mastrorilli Piero; Dell’Anna Maria Michela; Mali Matilda; Sisto Raffaello; Vignola Rodolfo (Archives of Environmental Protection, 2016)
Three different types of Fe(II)-modified natural zeolites were tested as supports in continuous-flow columns for the treatment of Cr(VI) contaminated water. The natural zeolites chosen as support were commercially available Zeosand (80% clinoptilolite), ATZ (79% phillipsite/chabazite), and ZS-55RW (90% Chabazite). All the examined modified zeolites turned out active for hexavalent chromium abatement, lowering its concentration below the European regulation level, even at relatively high flow rates (40 mL/h, linear velocity 15 cm/h). Zeosand, having a broader pH range of stability, was found to be the best one in terms of both Fe(II) uptake (0.54 wt%) and Cr removal (90 mg Cr/Kg zeolite).